Alternative schemes for twin-field quantum key distribution with discrete-phase-randomized sources - Li, Huaicong; Zhang, Chunmei (Frontiers in Physics, 2023)
The twin-field quantum key distribution (TF-QKD) protocol and its variants can overcome the well-known rate-loss bound without quantum repeaters, which have attracted significant attention. Generally, to ensure the security of these protocols, weak coherent states with continuous randomized phases are always assumed in the test mode. However, this assumption is difficult to meet in practice. To bridge the gap between theory and practice, we propose two alternative discrete-phase-randomized (DPR)-twin-field quantum key distribution protocols, which remove the phase sifting procedure in the code mode. Simulation results show that when compared with previous discrete-phase-randomized-twin-field quantum key distribution protocols, our modified protocols can significantly improve the secret key rate in the low channel loss range, which is very promising for practical twin-field quantum key distribution systems.